From Equivalence to Function: Pragmatic Approaches to Faithful Translation - Jepri, Jepri (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2025)
The concept of fidelity in translation has long been dominated by the pursuit of equivalence, whether formal, dynamic, or functional. However, recent developments in translation studies suggest that this paradigm may be insufficient to address the complexities of meaning, intention, and cultural context. This article argues for a reconceptualization of faithful translation through a pragmatic lens, emphasizing communicative purpose, contextual appropriateness, and cultural resonance over rigid equivalence. Drawing from theories such as Skopos Theory, Relevance Theory, and speech act pragmatics, the study explores how pragmatic considerations shape faithful translation as an interpretive and purpose-driven act. By analyzing examples from literary, legal, and intercultural translation scenarios, the article demonstrates how function-oriented approaches better accommodate nuanced intentions and audience expectations. This shift from equivalence to function does not imply a betrayal of the source text but rather a redefinition of fidelity as a dynamic negotiation of meaning across cultural and linguistic boundaries. The paper concludes by proposing a model of pragmatic fidelity that integrates context-sensitive strategies and ethical responsibility, offering a more adaptable and communicatively effective framework for modern translation practice.